Accuracy of manual palpation vs ultrasound for identifying the L3–L4 intervertebral space level in children. Issue 5 (28th January 2014) - Hayes, Jason; Borges, Bruno; Armstrong, Derek; Srinivasan, Ilavajady; Bosenberg, Adrian
Summary Background Insertion of needles into the spinal or epidural space is an important component of modern anesthetic practice. Needles are usually inserted at or below the L3–L4 intervertebral space to minimize the risk of spinal cord injury. Manual palpation is the most common method for identifying intervertebral spaces. However, anesthesiologists are increasingly using ultrasonography to guide the placement of regional, including neuraxial, anesthetic, and analgesic blocks. We undertook an observational study to compare the accuracy of manual palpation and ultrasound for determining the L3–L4 intervertebral space level. Methods Thirty children 0–12 years of age undergoing lumbar puncture were enrolled. For each subject, an anesthesiologist, using the landmark palpation method, determined the point on a radio‐opaque ruler that corresponded to the L3–L4 intervertebral space. A different anesthesiologist using the ultrasound method repeated this measurement. Fluoroscopy was then used to confirm the accuracy of each technique. The proportion of inaccurate measurements and the effects of anesthesiologists' experience, patient age, and size on the accuracy of each technique were compared. Results Thirty‐seven percent of measurements by the landmark palpation method were inaccurate by ≥1 levels cephalad to the L3–L4 intervertebral space. However, less experienced anesthesiologists (residents and fellows) made a disproportionate number of inaccurate measurements compared to consultants. Twenty‐three percent of measurements by the ultrasound method were inaccurate by ≥1 cephalad levels. The BMI‐for‐age percentile/weight‐for‐length percentile was higher in patients in whom either technique was inaccurate. Conclusion This observational study found no difference in the accuracy of landmark palpation, when performed by a consultant anesthesiologist, and ultrasound for determining the L3–L4 intervertebral space in children.